Floristic composition of two wetland forests in Araguaian Plain, State of Tocantins, Brazil, and comparison with other areas Composição floristica de duas florestas inundáveis na Planície do Araguaia, Estado do Tocantins, Brasil, e comparação com outras áreas - Sebastião Venâncio Martins; Elizabeth Rodrigues Brito; Ary Teixeira de Oliveira Filho; Alexandre Francisco da Silva; Elias Silva (Revista Árvore, 2008)
Seasonally inundated native forest fragments ("ipucas") located in natural landform depression swales of the Araguaian Plain are currently under land use pressure. Their composition needs to be better understood to guarantee their protection. This comparative study of fragments under different land use conditions was carried out at Lago Verde Farm, Lagoa da Confusão,Tocantins, Brazil. The location coordinates are UTM 643586 and 644060 East and 8792795 and 8799167 North. This study aimed to first analyze and compare the floristic composition of two seasonally inundated forest fragments of approximately one hectare each. The first is located in an intact (without human intervention) Gramineous-Woody Savanna region and the second in a rice cultivation region. The floristic composition of both fragments was then compared to that of other wetland forests located in the Northern, Central Western and Southeastern regions of Brazil.All the floristic compositions are affected by seasonal flooding and soil water saturation. The floristic inventory used a census method that sampled all trees and shrubs with perimeter at 1.30 m from soil (PAP) = 15cm; 665 individuals, 33 families and 49 species were recorded for the intact region and 807 individuals, 35 families and 70 species for the altered region fragment. The values of H' = 0.806 (Shannon-Weaver) and J = 3.44 nats /individual (equability) for the fragment in the region affected by rice cultivation are considered high compared to the intact region fragment values (H' = 0.761 and J = 2.97). Families contributing to floristic richness in the altered region fragment were Fabaceae (9 species), Vochysiaceae (6) and Annonaceae (4). In the intact region fragment, Fabaceae also presented the largest number of species (8) followed by Arecaceae, Chrysobalanaceae and Vochysiaceae (3 each). When comparing the forests from various regions in Brazil, floristic similarity was found to be small. Greater similarity was found when indices for the two Lagoa da Confusão fragments were compared to riparian forests located in the Federal District of Brasilia. Os fragmentos naturais de florestas inundáveis conhecidos como Ipucas localizam-se na planície do Araguaia, sob a forma de depressões naturais, estando atualmente sob forte pressão antrópica. Este estudo foi desenvolvido na fazenda Lago Verde, Lagoa da Confusão em Tocantins, entre as coordenadas UTM 643586 e 644060 leste e 8792795 e 8799167 norte. Os objetivos deste trabalho foram analisar e comparar a composição florística de dois fragmentos de florestas inundáveis de aproximadamente 1 ha cada, sendo um inserido em área de Savana Gramíneo-Lenhosa sem intervenção antrópica e outro em área de orizicultura, com outras florestas também sob influência de inundações sazonais e, ou, saturação hídrica do solo das Regiões Norte, Centro-Oeste e Sudeste. O levantamento florístico foi realizado através do método de Censo, em que foram amostrados todos os indivíduos arbustivo-arbóreos com perímetro a 1,30 m do solo (PAP) = 15 cm. Como resultado, foram apresentados 807 indivíduos, 35 famílias e 70 espécies na área antropizada e 665 indivíduos, 33 famílias e 49 espécies na área preservada. Os valores de H´ (Shannon-Weaver) e J (equabilidade) da área que está sob influência da orizicultura, 3,44 nats/indivíduo e 0,806, respectivamente, podem ser considerados altos em relação ao outro fragmento, onde os valores foram de 2,97 nats/indivíduo e 0,761. As famílias que contribuíram para a riqueza florística na floresta inundável com intervenção antrópica foram Fabaceae (9), Vochysiaceae (6) e Annonaceae (4). Na floresta inundável em área preservada, Fabaceae também apresentou maior riqueza, com oito espécies, seguidas de Arecaceae, Chrysobalanaceae e Vochysiaceae (3) cada. A similaridade florística foi baixa entre todas as florestas comparadas, porém maior semelhança foi encontrada entre florestas ripárias do Distrito Federal e entre as duas florestas inundáveis deste estudo.